Industry branding: attracting talent to weaker profile industries - Wallace, M.; Lings, I.; Cameron, Roslyn (John Wiley & Sons, 2012)
There is global competition for engineering talent with some industries struggling to attract quality candidates. The ‘brands’ of industries and organisations are important elements in attracting talent in a competitive environment. Using brand equity and signalling theory, this paper reports a quantitative study examining factors that attract graduating engineers and technicians to engineering careers in a weak brand profile industry. The survey measures graduating engineers’ preferences for career benefits and their perceptions of the rail industry, which has identified a significant skilled labour shortfall. Knowledge of young engineers’ preferences for certain benefits and segmenting preferences can inform branding and communications strategies. The findings have implications for all industries and organisations, especially those with a weaker brand profile and issues with attracting talent.